Contribution of Skill-Based Approach on Reading Achievement of EFL Students - Kusmartini, Sri Endah; Simanjuntak, Tiur (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
People can acquire valuable information for their lives if they have reading skills. Each individual has his own unique goal in reading. Therefore, some considerations need to be made to improve the skills especially regarding the approaches that can be used. One of the approach that can be applied in teaching reading is skill-based approach. Quantitative correlational study was employed to explore the contribution of skill-based approach on reading achievement of EFL students. The number of the respondents were eighty-one which were taken randomly from the students of Sriwijaya State Polytechnic semester two on the academic year 2023-2024. The questionnaire regarding skill-based approach and their reading scores were used to collect the data; and they were analyzed by using descriptive statistic, Pearson coefficient correlation and linear regression. Students’ perception regarding skill-based approach showed that 35.80% of the respondents have moderate perception; 45.68% have high perception, and 18.52% have a very high perception. In terms of reading achievement, 9.88% of respondents were sometimes able to comprehend; 56.79% were often able to comprehend reading; and 33.33% were usually able to comprehend reading. There was a significant but moderate correlation between the variables (R=0.493). The influence was significant and the contribution was 24.3%.